DENSIDADE DE SEMEADURA E ADUBAÇÃO NITROGENADA DE COBERTURA EM HÍBRIDOS DE MILHO COM DIFERENTES ARQUITETURAS - Serpa, Antoniele de Fatima (2016)
With the introduction of new corn genotypes in the market, with modern architecture of plants, characterized by lower size and erect leaves, it becomes very important to generate new research on technical information, such as the increase of plant densities, spacing reduction and levels of nitrogen as topdressing. In this sense, the objective of this research was to evaluate the commercial corn hybrids response, with modern and old architecture, under the influence of nitrogen as topdressing associated to different plant populations in the municipalities of Guarapuava and Laranjeiras do Sul, cities within Parana State. The treatments were evaluated individually, in two different cities: Guarapuava city, with row spacing of 0.45 m as well as Laranjeiras do Sul city, with row spacing of 0.90 m. The experimental design was a randomized block, with three replications, in a factorial scheme (6x3x3), where six corn hybrids were divided into twou different groups: First One - hybrids of modern architecture (AG8025Y, DKB 240Y, P1630H) and second one - hybrid of old architecture (P30R50H, DKB 390Y and P32R48H), three populations (60.000; 75.000; 90.000 plants ha-1) and three levels of nitrogen as topdressing (0; 90 and 180 kg ha-1 de N), using urea as a source, totaling 162 plots, during the 2012/2013 growing seasons. The leaf disease severity was evaluated: common rust (Puccinia sorghi); leaf spot diplodia (Stenocarpella macrospora) and helminthosporium (Exserohilum turcicum) in Guarapuava city, and agronomic characteristics in Guarapuava and Laranjeiras do Sul cities. The severity of common rust (Puccinia sorghi) was influenced by corn hybrid, plant density and topdressing dosage used. There were higher AUDPC for diplodia leaf spot (Stenocarpella macrospora) and helminthosporium (Exserohilum turcicum) in the corn hybrid of a modern plant architecture. The hybrid modern architecture scored lower insertion height of the first ear, plant height and stem diameter, that is dependent the experiment site, Guarapuava or Laranjeiras do Sul, when subjected to different doses of nitrogen as topdressign and seeding density. Nitrogen doses as topdressing and plant density influenced the weight of thousand grains of corn hybrids of modern and old architecture. The grain productivity was positively influenced by the increase as topdressing in fertilizer dosage and the plant architecture in experiment conducted in Guarapuava. The old architecture with increasing plant density negatively affected the ear diameter in Guarapuava (reduced) and positively in Laranjeiras do Sul (conventional). Nitrogen as topdressing of 180 kg ha-1 de N reduced the number of row of hybrid grains DKB 240Y and number of grains per row of DKB 390Y corn hybrid, in experiment conducted in Guarapuava.